2016
DOI: 10.1007/s00401-016-1642-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in T cell cytotoxicity and cell death mechanisms between progressive multifocal leukoencephalopathy, herpes simplex virus encephalitis and cytomegalovirus encephalitis

Abstract: During the appearance of human immunodeficiency virus infection in the 1980 and the 1990s, progressive multifocal leukoencephalopathy (PML), a viral encephalitis induced by the JC virus, was the leading opportunistic brain infection. As a result of the use of modern immunomodulatory compounds such as Natalizumab and Rituximab, the number of patients with PML is once again increasing. Despite the presence of PML over decades, little is known regarding the mechanisms leading to death of infected cells and the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
4
19
1
1
Order By: Relevance
“…In this study, we sought to explore the effect of Bcl‐2 on cellular oxidative damage that results from HQ. PARP‐1 not only has been reported to be present in the nucleus but also has been found to translocate to the cytoplasm [Laukoter et al, ]. Here, we found that both Bcl‐2 and PARP‐1 translocated from the nucleus to the cytoplasm after HQ‐induced oxidative damage.…”
Section: Introductionsupporting
confidence: 62%
“…In this study, we sought to explore the effect of Bcl‐2 on cellular oxidative damage that results from HQ. PARP‐1 not only has been reported to be present in the nucleus but also has been found to translocate to the cytoplasm [Laukoter et al, ]. Here, we found that both Bcl‐2 and PARP‐1 translocated from the nucleus to the cytoplasm after HQ‐induced oxidative damage.…”
Section: Introductionsupporting
confidence: 62%
“…The vast majority of human acute and chronic inflammatory brain diseases, however, reflect an inflammatory reaction, massively dominated by MHC Class I restricted CD8 + T-lymphocytes (Machado-Santos et al, 2018). In some of these diseases, such as paraneoplastic encephalitis (Dauvilliers et al, 2013), Rasmussen's encephalitis (Bien et al, 2002), and viral encephalitis (Cox, Kahan, & Zajac, 2013;Laukoter et al, 2017), evidence for tissue injury and elimination of infected cells, which is directly mediated by cytotoxic CD8 + lymphocytes, has been provided. Only few groups so far have developed experimental models, which reflect brain inflammation by CD8 + T-cells.…”
Section: The Spectrum Of Inflammatory Diseases Of the Brain And Spimentioning
confidence: 99%
“… Note : The table compares the key features of inflammatory lesions in the central nervous system mediated by different T‐cell populations, B‐cells, and innate immunity in rodent models and humans, also describing the reaction patterns of microglia/macrophages and astrocytes. References 1: Ajami et al (), 2: Ben‐Nun, Wekerle, and Cohen (), Lassmann et al (), 4: Wolf et al (), 5: Blaabjerg et al (). 6: Mayo et al (), 7: Basso et al (). 8: Bradl and Lassmann (), 9: Linington, Bradl, Lassmann, Brunner, and Vass (), 10: Misu et al (), 11: Pohl et al, , 12: Storch et al (). 13: Bien et al (), 14: Cabarrocas, Bauer, Piaggio, Liblau, and Lassmann (), 15: Dauvilliers et al (), 16: Ji, Perchellet, and Goverman (), 17: Laukoter et al (), 18: Na et al (), 19: Saxena et al (), 20: Steinbach et al (), 21: Tröscher et al (). 22: Machado‐Santos et al (), 23: van Nierop et al (), 24: Zrzavy et al (). 25: Felts et al (), 26: Marik, Felts, Bauer, Lassmann, and Smith (), 27: Nau and Brück (2002). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, HSE patient mutations in the transcription factor genes STAT1 and IRF3 (15,16), as well as in the essential NF-kB modulator NEMO (17), further reinforce the importance of IFN in mounting a protective response to HSV-1 neuroinvasion. Although antiviral therapy is used to control CNS viral replication and treat HSE, it cannot mitigate the risk of sequelae incurred through the breakdown of the BBB, infiltration of leukocytes, or elevated caspase-dependent neuronal cell death at sites of infection and neuroinflammation (18,19). Even in patients who have fully recovered from HSE, the extensive infiltration of activated CD68 + myeloid cells and of CD3 + T cells, including many cytotoxic CD8 + T cells, may persist long after HSV-1 viral clearance from the CNS (20).…”
mentioning
confidence: 99%